Long-term safety and efficacy of anti-tumor necrosis factor-alpha biosimilar agents in the treatment of psoriasis: a single center study. (19th May 2022) - Ricceri, Federica; Rosi, Elia; Di Cesare, Antonella; Scandagli, Ilaria; Fastame, Maria Thais; Prignano, Francesca
Abstract: Biosimilar anti-tumor necrosis factor (TNF)-alpha drugs are widely used in the treatment of psoriasis, but only few studies reported the long-term experience of the various biosimilar agents in the real world practice. A monocentric retrospective observational study was performed to assess the long-term efficacy, tolerability, and safety of biosimilars adalimumab (bADA), biosimilar etanercept (bETN), and biosimilar infliximab (bIFX) in psoriasis patients. A total of 73 patients (19 patients treated with bADA, 37 with bETN and 17 with bIFX) were enrolled and observed up to 48 months of follow-up. Regarding the efficacy, across all biosimilar treatments combined, the mean PASI score was ≤2 (1.2) after 12 months of treatments. Notably, the mean PASI score remained relatively stable during all 48 months of follow-up. With regard to tolerability and safety in the present study, 34 (28%) patients experienced adverse events during all biosimilar therapy, and three (4.3%) discontinued treatment. No severe adverse events, death, or malignancy cases were recorded during the study period. Our results support that biosimilar anti-TNF-alpha drugs are effective and well tolerated drugs for the long-term treatment of psoriasis.